The taxonomic and phylogenetic relationships of Trypanosoma vivax from South America and Africa - Cortez, A. P.; Ventura, R. M.; Rodrigues, A. C.; Batista, J. S.; Paiva, F.; Añez, N.; Machado, R. Z. [UNESP]; Gibson, W. C.; Teixeira, M. M G (Cambridge University Press (CUP), 2006)
The taxonomic and phylogenetic relationships of Trypanosoma vivax are controversial. It is generally suggested that South American, and East and West African isolates could be classified as subspecies or species allied to T. vivax. This is the first phylogenetic study to compare South American isolates (Brazil and Venezuela) with West/East African T. vivax isolates. Phylogeny using ribosomal sequences positioned all T. vivax isolates tightly together on the periphery of the clade containing all Salivarian trypanosomes. The same branching of isolates within T. vivax clade was observed in all inferred phylogenies using different data sets of sequences (SSU, SSU plus 5.8S or whole ITS rDNA). T. vivax from Brazil, Venezuela and West Africa (Nigeria) were closely related corroborating the West African origin of South American T. vivax, whereas a large genetic distance separated these isolates from the East African isolate (Kenya) analysed. Brazilian isolates from cattle asymptomatic or showing distinct pathology were highly homogeneous. This study did not disclose significant polymorphism to separate West African and South American isolates into different species/subspecies and indicate that the complexity of T. vivax in Africa and of the whole subgenus Trypanosoma (Duttonella) might be higher than previously believed. © 2006 Cambridge University Press.
Keywords: Brazil; East Africa; Evolution; Genetic diversity; Phylogeny; Ribosomal genes; South America; Taxonomy; Trypanosoma vivax; West Africa; ribosome DNA; Africa; cladistics; controlled study; evolution; genetic analysis; genetic variability; genus; geographic distribution; Kenya; nonhuman; parasite isolation; phylogeny; priority journal; ribosome; RNA sequence; taxonomy; Venezuela; Animals; Base Sequence; Cattle; DNA, Protozoan; DNA, Ribosomal; Geography; Molecular Sequence Data; Polymerase Chain Reaction; Polymorphism, Genetic; Sequence Alignment; Sheep; Bos taurus; Duttonella; Trypanosoma